1995
DOI: 10.1111/j.1365-2818.1995.tb03586.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of image formation for thick biological specimens: exit wavefront reconstruction and electron energy‐loss spectroscopic imaging

Abstract: SUMMARY With increasing frequency, cellular organelles and nuclear structures are being investigated at high resolution using electron microscopic tomography of thick sections (0·3–1·0 μm). In order to reconstruct the structures in three dimensions accurately from the observed image intensities, it is essential to understand the relationship between the image intensity and the specimen mass density. The imaging of thick specimens is complicated by the large fraction of multiple scattering which gives rise to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 25 publications
(21 reference statements)
2
19
0
Order By: Relevance
“…for thick specimens showed significant phase contrast, and this contribution dominates for resolutions better than 10 nm (Han et al, 1995). These findings are confirmed by the data shown in Fig.…”
Section: Phase and Amplitude Contrast Of Thick Objectssupporting
confidence: 92%
See 1 more Smart Citation
“…for thick specimens showed significant phase contrast, and this contribution dominates for resolutions better than 10 nm (Han et al, 1995). These findings are confirmed by the data shown in Fig.…”
Section: Phase and Amplitude Contrast Of Thick Objectssupporting
confidence: 92%
“…Producing sharp images and strong contrast at the same time is the main advantage of the novel HPC technique over conventional defocus CET. Han et al (1995) showed that the problem of weak phase contrast persists for thick specimens (0.3-1 lm), such as ice-embedded cells or organelles as they are analyzed in CET. Objects with a thickness above 0.5 lm cause about 60% inelastic scattering which can be partially converted into amplitude contrast by energy filtering (Angert et al, 2000).…”
Section: Quantification Of Signal Loss and Pctf Phase Shiftmentioning
confidence: 99%
“…With increasing specimen tilt angle 0 (equivalent to an increasing effective specimen thickness following 1 / cos 9), the average image intensity decreases logarithmically (data not shown). This is in agreement with the logarithmic decrease of the elastically scattered electrons as a function of specimen thickness (Han et al, 1995c). Both of these observations are consistent with the absorption model for thick specimens.…”
Section: Restoration Of Thick Amorphous Specimenssupporting
confidence: 88%
“…Studies have shown that the 3D power spectrum of a through focus series (taken at equal intervals as in the exit wavefront reconstruction) can be used to evaluate the proportion of coherent electrons contributing to imaging (Han et aL, 1995c). By combining this technique with ESI, it was shown that for thick biological specimens, only the elastically (zero energy-loss) scattered electrons exhibit the linear imaging behavior through focus, which is characteristic of the coherent image component (Han et ai, 1995b).…”
Section: Aberrations Contributed By Electron-specimen Interactionsmentioning
confidence: 99%
“…This could be circumvented by lowering the dose, however, the main drawback of this method remains that even at higher defoci the contrast-transfer function sin x will not provide a good contrast for larger spacings. Nevertheless, Han et al (1995) reported about the mechanism of image formation for thick biological specimens at 200 and 300 keV in order to resolve the coherent scattering component from the incoherent (multiple scattering) components by exit wavefront reconstruction using a throughfocus series. They found that although it is commonly assumed that image formation of thick specimens is dominated by amplitude (absorption) contrast, that for conventionally stained biological specimens phase contrast contributes significantly, and that at resolutions better than similar to 10 nm, superposed phase contrast dominates.…”
Section: Discussionmentioning
confidence: 98%